2010
DOI: 10.1111/j.1747-0803.2010.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Device Closure of Patent Ductus Arteriosus in Marfan Patients: Safety and Effect on the Aortic Root Diameter

Abstract: We concluded that PDA device closure in Marfan patients is safe. Risk of residual shunt is higher even after closure of small ducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…in research for monitoring aortic root dimensions through time [51,52]. Niwa et al defined aortic dilation when this ratio was >1.5, found in 15% of their patients [11].…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…in research for monitoring aortic root dimensions through time [51,52]. Niwa et al defined aortic dilation when this ratio was >1.5, found in 15% of their patients [11].…”
Section: Parametersmentioning
confidence: 99%
“…These arteries increase aortic flow and theoretically may contribute to the aortic dilation [11]. In a small cohort of Marfan patients, it was shown that closure of even small patent ductus arteriosus may negatively affect aortic dimensions in at least some Marfan patients [52]. Although there is no direct evidence for this recommendation, occlusion of residual collateral arteries seems to be prudent in these patients with aortic dilation.…”
Section: Aortopulmonary Shuntsmentioning
confidence: 99%